Species Diversity of Lichen as A Bioindicators of Air Quality at The State Polytechnic of Jember - Agustin, Mili; Avika Aditya Febriana Putri; Ika Nuraini; Yohana Maharani Pitaloka; Putri Saniyyah Rahmalisa Az Zahra; Retno Wimbaningrum; Rendy Setiawan (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
Lichens are symbiotic organisms that are sensitive to changes in air quality, so they are widely used as environmental bioindicators. The purpose of this study was to determine the diversity of lichens in the Jember State Polytechnic area and to assess air quality based on the Atmospheric Purity Index (API). The research was conducted at nine observation sites using a purposive sampling method with 10 × 10 cm plots on four sides of tree trunks at each point. Lichen samples were collected, identified based on morphological characteristics, and their coverage percentage was calculated to obtain frequency values and ecological indices used in the ACI calculation. The results showed that 25 types of lichens were found with a coverage area of 8.647%. The highest ACI value was found in the Department of Language, Communication, and Tourism with a value of 0.35, while the lowest values were found in the Department of Information Technology and the Department of Agribusiness Management with ACI values of 0.02, respectively. All locations on campus had very low IAP values with a total value of 0.86, indicating a very high level of air pollution. The location with the highest IAP value remained in the very high pollution category. The low IAP value is strongly suspected to be related to the high level of motor vehicle activity on campus and the suboptimal function of vegetation in reducing atmospheric pollutants. Keywords: Air Quality, Atmospheric Purity Index, Bioindicator, Lichen